The Effect of Job Demands on Burnout Among Employees of PT PLN on Madura Island with Job Resources as an Intervening Variable - Angger Yulia Putra; Endang Suswati; Sugeng Mulyono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study addresses the significant challenge of employee burnout, exacerbated by excessive job demands in the post-pandemic era, particularly within essential public service sectors like energy. Focusing on the unique, geographically isolated context of PT PLN on Madura Island, the research examines the direct influence of job demands on burnout and investigates the intervening role of job resources as proposed by the Job Demands-Resources (JD-R) theory. The primary objectives were to analyze the direct effect of job demands on burnout, test the moderating role of job resources, and explore the contextual influence of managerial discretion. A quantitative survey method was employed, utilizing a saturated sample of 125 employees across all PLN units in Madura. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed complex dynamics: while all hypothesized paths were statistically significant, their directions contradicted conventional JD-R theory. Job demands had a significant negative effect on burnout, and job resources also showed a significant negative relationship with burnout. Only the positive effect of job demands on job resources aligned with theoretical expectations. These unexpected findings underscore the critical role of specific contextual factors such as remote location, socio-cultural norms, and organizational bureaucracy in reshaping well-known psychological pathways, suggesting that standardized interventions may be ineffective without contextual adaptation